Interferon-λ3 Exacerbates the Inflammatory Response to Microbial Ligands: Implications for SARS-CoV-2 Pathogenesis - Read SA; Gloss BS; Liddle C; George J; Ahlenstiel G (Dove Medical Press, 2021)
Scott A Read,1– 3 Brian S Gloss,4 Christopher Liddle,3 Jacob George,3 Golo Ahlenstiel1– 3 1Blacktown Clinical School, Western Sydney University, Blacktown, NSW, 2148, Australia; 2Blacktown Hospital, WSLHD, Blacktown, NSW, 2148, Australia; 3Storr Liver Centre, The Westmead Institute for Medical Research, The University of Sydney and Westmead Hospital, Westmead, NSW, 2145, Australia; 4Westmead Research Hub, Westmead Institute for Medical Research, Westmead, NSW, 2145, AustraliaCorrespondence: Scott A Read Email s.read@westernsydney.edu.auIntroduction: Interferon lambdas (IFN-λs) are antiviral cytokines that restrict pathogen infection and dissemination at barrier surfaces. Controlled expression of IFN-λs efficiently eliminates acute infections by activating a suite of interferon stimulated genes that inhibit viral propagation and activate local immune cells. Excessive or prolonged production of IFN-λs can however mediate tissue inflammation and disrupt epithelial barriers in both viral and non-viral disease. The mechanism by which IFN-λs drive this disease pathogenesis is poorly understood but may be caused by IFN-λ-mediated amplification of other innate immune signaling pathways.Methods: Monocyte-derived macrophages were differentiated ± IFN-λ 3 and treated with KDO-lipid A, poly I:C or zymosan, representing bacterial, viral or fungal ligands, respectively. Transcriptome and protein expression were quantified by RNA sequencing/PCR and ELISA/bead array, respectively. Bioinformatic analysis was used to define transcription factor profiles and signaling pathways amplified by IFN-λ 3. Finally, the SARS-CoV-2 dataset GSE152075 was queried to compare the effects of IFNL versus IFNA expression in relation to viral load and nasopharyngeal transcriptomes.Results: IFN-λ 3 exacerbated inflammatory and chemotactic responses unique to each microbial ligand, as measured by RNA sequencing and by ELISA/bead array. Functional annotation identified pathways amplified by IFN-λ 3, including inflammasome activation. Inflammasome amplification was confirmed in vitro, as measured by caspase 1 activity and IL-1β cleavage. Lastly, SARS-CoV-2 infected nasopharyngeal transcriptomes expressing IFN-λs but not IFN-αs were implicated in myeloid cell-driven pathogenesis including neutrophil degranulation, complement and coagulation cascades.Discussion: These data suggest that IFN-λs contribute to disease pathology by exacerbating innate immune responses during chronic or severe disease states. IFN-λs may contribute to SARS-CoV-2 disease severity, however further study is required to confirm true causation.Keywords: interferon lambda, inflammation, COVID-19, innate immunity